New Cases of Andean Cutaneous Leishmaniasis in the Quinocay District, Yauyos Province, Lima - Bobbio Pérez, Milko (2000)
Five patients with the diUgnosis of Andean Cutaneous Leishmaniasis were seen in the District of Quinocay, between may 1999 and january 2000, after a lateney period of 8 years. All the patients were women, lesions were located on the face and lower limbs with 1-2 cm of size and the main symptom was itching without infection signs. Response to pentavalent antimony therapy was good.